Adhesive Leaf Created by a Corona Discharge - Lee, Wonseok (Sci Rep, 2018)
Here, we report a new concept of both the adhesive manner and material, named “adhesive leaf (AL),” based on the leaf of the plant Heteropanax fragrans. The treatment of the corona discharge on the leaf surface can cause the nano-/microdestruction of the leaf epidermis, resulting in an outward release of sap. The glucose-containing sap provided the AL with a unique ability to stick to various substrates such as steel, polypropylene, and glass. Moreover, we reveal that the AL adhesion strength depends on the AL size, as well as the corona-discharge intensity. Conventional adhesives, such as glue and bond, lose their adhesive property and leave dirty residues upon the removal of the attached material. Unlike the conventional methods, the AL is advantageous as it can be repeatedly attached and detached thoroughly until the sap liquid is exhausted; its adhesive ability is maintained for at least three weeks at room temperature. Our findings shed light on a new concept of a biodegradable adhesive material that is created by a simple surface treatment.